6ER-007 Off-label use of dalbavancin in gram-positive infections: effectiveness, safety and cost in clinical practice. (March 2019) - Chamorro-De Vega, E; Rodriguez-Gonzalez, CG; Rochet, ME; Valerio, M; Olmedo, M; Herranz-Alonso, A; Munoz, P; Sanjurjo-Saez, M
Abstract : Background: Dalbavancin (DAL) has recently been approved to treat complicated skin and soft tissue infections. It enables treatments with a single IV administration, so it is a highly attractive option in other infections that requires long-term treatment. Purpose: To provide information on the effectiveness and safety of DAL in off-label indications under clinical practice, and its impact on reduction of length of hospital stay and hospital costs. Material and methods: Study design: prospective cohort study. Inclusion criteria: all adult patients who received at least one dose of DAL between 1 January 2018 and 31 August 2018 in a tertiary hospital in Spain. Effectiveness was assessed by clinical success (resolution of signs and symptoms related to bacterial infections without microbiological evidence of infection during the follow-up period). Safety was evaluated by the incidence of adverse drug events (ADE). Cost was estimated taking into account the cost of the antibiotic therapy, the cost of hospital stay and the cost of nursing visits. Follow-up: at least 1 month after DAL therapy was discontinued. Results: A total of 19 patients received DAL for an off-label indication during the study period (60.9% males; median age 59 years). All patients received DAL as targeted therapy. The most common indications were: endocarditis (n=6), bacteraemia (n=6), osteomyelitis (n=2), espondilodiscitis (n=2), other endovascular infections (n=2) and pneumonia (n=1). These infections were mainly caused by Staphylococcus aureus (10 isolates), coagulase-negative staphylococci (six isolates) and Enterococcus spp (three isolates). All patients received previous antibiotics for a median of 19 days. DAL was administered for a median of 39 days (range 15–150 days), and concomitant antimicrobial therapy was prescribed to 10 patients (53%). The administration of DAL allowed immediate patient discharge in 73% of patients. The overall clinical success rate of DAL was 89%. Adverse events, mainly mild in intensity, were reported in six patients. The total cost of DAL was €62 179. Overall, DAL was estimated to reduce hospitalisation by 273 days, with an estimated overall cost reduction of €67 466 (€3551 per patient). Conclusion: DAL appears to be an effective and safe therapy in several serious gram-positive infections. Its use to facilitate hospital discharge can potentially lead to cost savings. References and/or acknowledgements: http://dx.doi.org/10.1136/ejhpharm-2018-eahpconf.160 No conflict of interest.